GAUCHER’S DISEASE - O. S. Gundobina; E. V. Komarova; L. S. Namazova-Baranova; А. K. Gevorkyan; G. B. Movsisyan (Педиатрическая фармакология, 2013)
The article gives data on epidemiology, pathogenesis, modern classification and the main clinical manifestations of Gaucher’s disease in children; it also gives criteria of differential diagnostics with other diseases. The article shows that the only effective method of treating Gaucher’s disease is pathogenic enzyme-substitutive therapy which arrests the main clinical manifestations of the disease improving life quality of patients without pronounced side effects. Imiglucerase is used for such treatment; it causes hydrolysis of glucocerebroside into glucose and ceramide (regular metabolism of membrane lipids). Imiglucerase is indicated for long-term enzyme-substitutive therapy in patients with confirmed Gaucher’s disease (types 1 and 3). It is recommended to monitor condition of patients in the setting of therapy in compliance with the requirements of the International Collaborative Gaucher Group. The article cites the main mistakes of diagnostics and management of such patients and ungrounded prescriptions when treating this disease.